Stereoscopic image distortion in radial camera and projector configurations - Son, Jung-Young; Gruts, Yuri N.; Kwack, Kae-Dal; Cha, Kyung-Hun; Kim, Sung-Kyu (OPTICAL SOC AMER, 2007)
A closed-form solution of describing perceived image in stereoscopic imaging systems with radial recording and projecting geometry for arbitrary viewer positions is presented. This solution is derived by finding a condition for making the heights of homolog points in both left and right images projected on the screen in the geometry equal. The solution has the same equation form as that of the parallel geometry except that it has a constant shifting term in the horizontal direction. This term is a main source for distortions in the perceived image. The condition of eliminating the term makes the solution the same as that for stereoscopic imaging systems with parallel recording and projecting geometry. (c) 2007 Optical Society of America.